Collision avoidance strategies for unmanned aerial vehicles in formation flight - Seo, Joongbo; Kim, Youdan; Kim, Seungkeun; Tsourdos, Antonios (IEEE, 2017)
Collision avoidance strategies for multiple UAVs (Unmanned Aerial Vehicles) based on geometry are investigated in this study. The proposed strategies allow a group of UAVs to avoid obstacles and separate if necessary through a simple algorithm with low computation by expanding the collision-cone approach to formation of UAVs. The geometric approach uses line-of-sight vectors and relative velocity vectors where dynamic constraints are included in the formation. Each UAV can determine which plane and direction are available for collision avoidance. An analysis is performed to define an envelope for collision avoidance, where angular rate limits and obstacle detection range limits are considered. Based on the collision avoidance envelope, each UAV in a formation determines whether the formation can be maintained or not while avoiding obstacles. Numerical simulations are performed to demonstrate the performance of the proposed strategies.
Keywords: Collision avoidance; Aircraft; Geometry; Military aircraft; Unmanned aerial vehicles; Heuristic algorithms; Real-time systems